2017
DOI: 10.1002/aelm.201700329
|View full text |Cite
|
Sign up to set email alerts
|

Sb2Se3 Thin‐Film Photovoltaics Using Aqueous Solution Sprayed SnO2 as the Buffer Layer

Abstract: Sb2Se3 is a promising photovoltaic material due to its suitable bandgap, strong light absorption, simple phase, nontoxicity, and earth‐abundant constituents. Currently, most Sb2Se3 thin‐film solar cells are based on toxic CdS as the buffer layer. Here, for the first time, non‐toxic, wide‐bandgap, and chemically stable SnO2 is introduced as the buffer layer instead of CdS to build superstrate SnO2/Sb2Se3 thin‐film solar cells. The phase of sprayed SnO2 films and device band alignment are investigated in detail.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…For example, a CdS ETL works best for Sb 2 Se 3 solar cells, and Sb 2 S 3 and Sb 2 (S x Se 1−x ) 3 solar cells based on SnO 2 ETL generally show better performances. It's noted that Sb 2 Se 3 solar cells using an high‐temperature solution processed SnO 2 as an ETL delivered low efficiency compared with those of CdS and ZnO ETLs . Based on our understanding of SnO 2 from previous review papers, we believe the reason for this low efficiency is that high‐temperature processed SnO 2 ETL cannot effectively block holes compared with the low‐temperature processed ETLs, leading to severe interface recombination and shunt paths.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, a CdS ETL works best for Sb 2 Se 3 solar cells, and Sb 2 S 3 and Sb 2 (S x Se 1−x ) 3 solar cells based on SnO 2 ETL generally show better performances. It's noted that Sb 2 Se 3 solar cells using an high‐temperature solution processed SnO 2 as an ETL delivered low efficiency compared with those of CdS and ZnO ETLs . Based on our understanding of SnO 2 from previous review papers, we believe the reason for this low efficiency is that high‐temperature processed SnO 2 ETL cannot effectively block holes compared with the low‐temperature processed ETLs, leading to severe interface recombination and shunt paths.…”
Section: Discussionmentioning
confidence: 92%
“…Interfacial Engineering : Interfacial engineering improvements of planar Sb 2 Se 3 solar cells were mainly focused on developing alternative ETLs or highly efficient HTLs. Apart from the widely used CdS, TiO 2 and ZnO ETLs, wide‐bandgap Mg‐doped ZnO and SnO 2 have been demonstrated to work as efficient alternative ETLs for planar Sb 2 Se 3 heterojunction solar cells . Recently, PbS colloidal quantum dot films were used as HTLs for planar Sb 2 Se 3 solar cells, which not only minimizes the carrier recombination loss at the back contact and boosts the carrier transport efficacy but also contributes to the photocurrent by its own near‐infrared absorption …”
Section: Antimony Chalcogenide Solar Cellsmentioning
confidence: 99%
“…Materials and device characterization are similar to our previous reports . The morphologies and EDS characterization of Sb 2 (Se 1−x S x ) 3 films were checked by scanning electron microscopy (FEI Nova NanoSEM450, without Pt coating).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that the transportation of electrons between the absorber layer and the electron transporting layer can make a great influence on the PCE of Sb 2 (S,Se) 3 thin film solar cells by tuning the band gap offset at the interface . In addition, series works basing on various electron transporting layer have been carried out by Tang's group, which revealed that the selection of a better electron transporting layer for Sb 2 (S,Se) 3 thin film solar cells is very important. But so far few works were carried out on the band gap engineering between Sb 2 (S,Se) 3 absorber layer and n type films.…”
Section: Introductionmentioning
confidence: 99%